Konsep Diversi dan Restorative Justice sebagai Pergeseran Tanggung Jawab Pidana pada Sistem Peradilan Pidana Anak - Utami, Pangestika Rizki (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2018)
The concept of diversity and restorative Justice is a criminal cases settlement form that provide children protection by promoting the best interest of the child principle. To protect children from the formal process of criminal justice system, the legal and humanitarian experts conceptualize the act of removing child who has allegedly committed a criminal offense from the general criminal justice process by providing an alternative punishment that is considered better for children. The concept of diversion is created based on the fact that the criminal justice process for children as the perpetrators through the conventional criminal justice system causes more harm than good. Restorative Justice is a fair resolving criminal cases system with by emphasizing recovery in its original state. This article will discuss about the shifting of children criminal responsibility from conservative criminal penalties to child friendly criminal penalties with the concept of diversity and restorative justice.